2021
DOI: 10.7150/thno.66518
|View full text |Cite
|
Sign up to set email alerts
|

Clinically translatable gold nanozymes with broad spectrum antioxidant and anti-inflammatory activity for alleviating acute kidney injury

Abstract: Rationale: Acute kidney injury (AKI) is associated with aberrant generation of oxidative species and inflammation, leading to high mortality of in-hospitalized patients. Although N -acetylcysteine (NAC) showed positive effects in alleviating contrast-induced AKI, the clinical applications are strongly restrained due to the low bioavailability, low renal accumulation, short renal retention time, and high dosage-induced toxicity. Methods: We addressed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 68 publications
(43 reference statements)
1
30
0
Order By: Relevance
“…More importantly, lots of noble metal nanoparticles have high intrinsic catalytic activity due to their incompletely filled d-electron orbitals and small energy level spacing [ 212 ]. Currently, ultra-small-sized gold [ 198 ], platinum [ 195 ], Ir [ 196 ], and Ru [ 197 ] nanoparticles have been developed for the treatment of AKI, and these nanoparticles are often passively targeted to renal tissue to eliminate various RONS thanks to their variety of antioxidant enzyme properties. Among them, platinum nanoparticles (Pt NPs) have attracted much attention for their broad-spectrum and efficient RONS quenching activity by mimicking a variety of enzymes, including CAT, SOD, and NADH-coenzyme Q reductase.…”
Section: Antioxidant Nanozymesmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, lots of noble metal nanoparticles have high intrinsic catalytic activity due to their incompletely filled d-electron orbitals and small energy level spacing [ 212 ]. Currently, ultra-small-sized gold [ 198 ], platinum [ 195 ], Ir [ 196 ], and Ru [ 197 ] nanoparticles have been developed for the treatment of AKI, and these nanoparticles are often passively targeted to renal tissue to eliminate various RONS thanks to their variety of antioxidant enzyme properties. Among them, platinum nanoparticles (Pt NPs) have attracted much attention for their broad-spectrum and efficient RONS quenching activity by mimicking a variety of enzymes, including CAT, SOD, and NADH-coenzyme Q reductase.…”
Section: Antioxidant Nanozymesmentioning
confidence: 99%
“…14 C). Very recently, Zhang et al employed the NAC as a reductant and capping to synthesize ultrasmall gold nanoclusters (Au NCs) to provide effective AKI alleviation [ 198 ]. Au NCs had multienzyme mimetic properties like POD, SOD, and CAT.…”
Section: Antioxidant Nanozymesmentioning
confidence: 99%
“…These findings proved that ultrasmall Ir NPs-PVP have good compatibility and low toxicity, and have enormous promise for treating cisplatin-induced AKI and RM-AKI. Zhang et al also designed ultrasmall gold nanoclusters capped with NAC (Au-NAC) with SOD-like, CAT-like, and POD-like activities for RM-AKI treatment 184 (Fig. 17(d)).…”
Section: Acute Kidney Injurymentioning
confidence: 99%
“…Gold nanoparticles (Au NPs) have shown good biocompatibility, water-solubility, catalytic activity and great potential as self-therapeutic nanosystems for drug delivery platforms against inflammatory disorders, including AKI and RA due to their anti-inflammatory and antioxidative performances [ 179 , 180 ]. It has been reported that the tunable bio-effects of Au NPs differ across research due to the application of regulatory particle sizes and surface modification [ 181 ].…”
Section: Latest Developments Of Biomaterials For Psoriasis Therapiesmentioning
confidence: 99%